The role of behavioral type composition on resource use and growth of a juvenile predator. (30th April 2022) - Nannini, Michael A; Parkos, Joseph J; Wahl, David
Abstract: Juvenile largemouth bass have distinct behavioral types that separate along the exploring behavioral axis and differ in diet. We used a mesocosm experiment to test the hypothesis that groups composed of mixed behavioral types would have more efficient use of prey resources and reduced competition between individuals than experimental populations composed of similar behavioral types. Fish growth, diets, and prey composition were quantified over a 4-week period in mesocosms containing prey communities that were mixtures of zooplankton from the pond water used to fill them and natural colonization by terrestrial insects. Mesocosms contained juvenile largemouth bass of either all fast exploratory-type, all slow exploratory-type, or a 50/50 mix of the two behavioral types. Treatments with similar behavioral types had lower growth than treatments with mixed behavioral types. While evidence showed that slow explorers in homogeneous groups consumed fewer macroinvertebrates outside of refuge habitat, the same was not true of fast explorers. Results suggest that populations composed of different compositions of behavioral types may also differ in their food web interactions. Potential alternative explanations for the difference in growth between mixed versus homogeneous communities include higher activity, increased antagonistic interactions and the role of social cues that might signal when it is safe to begin foraging after exposure to a predator. The differences in growth suggest that individual performance can be higher in populations with a balanced mixture of behavioral types compared to more homogenous populations and adds to the growing knowledge that individual behavioral traits can have emergent population-level effects. Abstract : Populations composed of diverse behavioral types are better for individual growth. Distinct behavioral types expressed by individuals are widespread across nearly all animals. However, the ecological consequences of the ratio of different behavioral types within a population are poorly understood. The current work demonstrates that experimental populations with different behavioral types can have positive effects on growth compared to populations with similar behavioral types.